A structural study of alkaline earth metal complexes with hybrid disila-crown ethers. Issue 27 (30th November 2016) - Dankert, Fabian; Reuter, Kirsten; Donsbach, Carsten; von Hänisch, Carsten
Abstract : A series of disila-crown ether complexes have been characterized by single crystal X-ray diffraction. The complex stability of different systems were studied by DFT calculations and proton NMR experiments. Abstract : Compounds consisting of [M(1, 2-disila-[3 n ]crown- n )] 2+ (M = Mg, Ca, Sr, Ba; n = 5, 6) and [Ba(1, 2-disila-benzo[18]crown-6)] 2+ cations and different anions were obtained by equimolar reaction of the hybrid disila-crown ethers 1, 2-disila[15]crown-5 (1 ), 1, 2-disila[18]crown-6 (2 ) and 1, 2-disila-benzo[18]crown-6 (7 ) with alkaline earth metal salts. Even with strongly coordinating anions such as Br − or I − stable complexes could be obtained, showing the good coordination ability of these ligands. The structures of all coordination compounds were determined via single crystal X-ray diffraction (XRD). By means of DFT calculations, the complexation ability of 1, 2-disila[15]crown-5 (1 ) towards magnesium bromide was determined to be considerably higher compared to [15]crown-5. The opposite case was observed in solution as the exchange of calcium cations between [18]crown-6 and 1, 2-disila[18]crown-6 (2 ) was studied via dynamic proton nuclear magnetic resonance (NMR) spectroscopy.